A reappraisal of acute doses of benzodiazepines as a model of anterograde amnesia. (26th December 2020) - Segura, Isis Angélica; McGhee, Jamie; Della Sala, Sergio; Cowan, Nelson; Pompéia, Sabine
Abstract: Objective: Acute administration of benzodiazepines is considered a pharmacological model of general organic anterograde amnesias (OAA). We sought to determine which type of amnesia these drugs best model by comparing the effects of diazepam with those reported in amnesiacs regarding working memory capacity (WMC), susceptibility to retroactive interference (RI), and accelerated forgetting. Methods: In this double‐blind, parallel‐group design study, 30 undergraduates were randomly allocated to acute oral treatments with 15 mg diazepam or placebo. WMC and story recall were assessed pre‐ and post‐treatment. Story presentation was succeeded by 10 min of RI (spotting differences in pictures) or minimal RI (doing nothing in a darkened room). Delayed story recall was assessed under diazepam and 7 days later in a drug‐free session to assess accelerated forgetting. Results: Recall of stories encoded under diazepam, whether reactivated or not, was severely impaired (anterograde amnesia). However, diazepam did not impair WMC, increase susceptibility to RI, or accelerate forgetting. Conclusions: Diazepam's amnestic effects mirror those in patients with probable severe medial temporal damage, mostly restricted to initial consolidation and differ from other OAA (Korsakoff syndrome, frontal, transient epileptic, posttraumatic amnesia, and most progressive amnesias) in terms of WMC, susceptibility to RI and accelerated forgetting.